PEMANFAATAN LAPORAN POSISI KEUANGAN OLEH PENGGUNA DALAM PENGAMBILAN KEPUTUSAN (Studi Empiris pada Instansi Pemerintahan di Jawa Tengah) - Risalawati, Fitri; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to analyze the influence of education, experience, and social factors of the Statement of Financial Position utilization information for the users, especially the executive, legislative, and examiner on government agencies in Central Java in the planning decision-making, control and management. The study population consisted of leaders, supervisors, and inspectors as users of financial statement information in decision-making positions. The results showed that the variables of education, experience, and social factors and significant positive effect on the use of the information on the statement of financial position of government agencies in Central Java.